Neutrophil to Lymphocyte Ratio Predicts Poor Prognosis in Ischemic Cerebrovascular Disease - Celikbilek, Asuman (J Clin Lab Anal, 2013)
BACKGROUND: Inflammation plays a role in the pathogenesis of carotid atherosclerosis. Although previous data demonstrated an association between inflammatory biomarkers and stroke, there is no publication reporting the relation of neutrophil to lymphocyte (N/L) ratio with ischemic stroke. We aimed to analyze the predictive ability of N/L ratio in acute ischemic cerebrovascular disease. METHODS: A total of 190 patients including 70 patients with first‐ever atherothrombotic acute ischemic stroke (AAIS), 50 patients with transient ischemic attack, and 70 healthy subjects were enrolled in this study. We analyzed the values of white blood cell (WBC), N/L ratio, C‐reactive protein (CRP), gamma‐glutamyltransferase (GGT), homocysteine (HCY), mean platelet volume (MPV) in patients with ischemic group and compared those with control individuals. RESULTS: WBC, CRP, HCY, N/L ratio were found to increase significantly in AAIS patients than the controls (P < 0.001). With respect to mortality, there were no significant differences between the values of CRP, GGT, HCY, and MPV in patients with AAIS. However, WBC and N/L ratio values were found to increase significantly in dead patients (P = 0.024 and P = 0.029, respectively). A comparison of receiver operating characteristic curves among WBC, CRP, GGT, HCY, MPV, and N/L ratio variables was made. No significant differences were obtained between area under curve values (P > 0.05). A cut‐off value of 4.1 for N/L ratio was detected in predicting mortality with a sensitivity of 66.7% and a specificity of 74.1% (κ = 0.299, P = 0.006). CONCLUSIONS: These findings support the role of N/L ratio as a simple inexpensive and readily available marker of prognosis in acute ischemic stroke.